Notas sobre la agresión en el medio urbano: el caso de Zaragoza - Los Certales Palomar, Blanca; Cobo Plana, Juan Antonio (Geographicalia, 2017)
In this work it is laid out the forensic medical meeting structure could be a suitable source for the study of some aspects of the urban reality and its problems. It is analyzed the profile of the agression in 167 cases of injuries. It is a a previous communication of a multiple investigation project much ampler directed to the detection of the Zaragoza's urban violence, its factors, territorial aspects and its development through the time.
Keywords: Society; city; agression; violence; indicators.